Responses of necrophilous beetles to animal mass mortality in the Australian Alps - Rebecca L. Stone; Stefanie Bonat; Thomas M. Newsome; Philip S. Barton (Journal of Insect Conservation, 2023)
A diversity of insects can be found at the remains of dead animals (carrion) and they play a vital role in its decomposition and recycling. An emerging global problem with carrion is animal mass mortality events – the sudden, rapid die-off of many animals resulting in a large increase to the localised carrion resource pool. Yet, little is known about how insects respond to sudden and large inputs of carrion. We conducted an experiment in a mountainous alpine region of south-eastern Australia and compared beetle assemblages found at single carcass and mass mortality sites. We also examined the effects of vertebrate exclusion, and decomposition stage on beetles. We found 4,774 beetles representing 146 different species/morphospecies from 17 families. The most abundant species was Saprinus cyaneus cyaneus (Histeridae), and species of Staphylinidae and Silphidae also dominated the fauna, which is typical for necrophilous beetles in Australia. We also found a clear temporal change in beetle assemblages, with abundance and richness peaking during the active decay stage. We found that beetle abundance was greater at single carcasses than mass mortality sites, possibly as an artifact of sampling, and that species richness was similar among these two carcass treatment types. We found no significant effect of vertebrate exclusion on beetles, suggesting that large scavengers in the study system may not influence necrophilous insect communities around carrion. Implications for insect conservation: Our study highlights the diversity of beetles that can be found at carrion and their similar composition to the fauna found in other areas in the south-east of the Australian continent. Beetles may have reduced abundance at mass mortality sites which could affect their ability to contribute to carrion removal relative to smaller carrion quantities. Further research is required to quantify the role of other insects in carrion removal under a range of natural and mass mortality scenarios.